Pengertian pokok hukum dagang Indonesia V : Hukum pelayaran laut dan perairan darat 5 - PURWOSUTJIPTO, M N (Djambatan, 1989)
Pengertian pokok hukum dagang Indonesia. Hukum pelayaran laut dan perairan darat 5